Hardware/software co-design : principles and practice - Staunstrup, J. (Jørgen), 1952-; Wolf, Wayne Hendrix (Kluwer Academic Publishers, 1997)
Hardware/Software Co-Design, Principles and Practice presents a number of issues of fundamental importance for the design of integrated hardware software products such as embedded, communication, and multimedia systems. This book is a comprehensive introduction to the fundamentals of hardware/software co-design. Co-design is still a new field but one which has substantially matured over the past few years. This book, written by leading international experts, covers all the major topics. Hardware/Software Co-Design, Principles and Practice contains sufficient material for use by teachers and students in an advanced course of hardware/software co-design. It also contains extensive explanation of the fundamental concepts of the subject and the necessary background to bring practitioners up-to-date.